Faut-il en finir avec la Charte de Venise ? - Claudine Houbart (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Each anniversary of the Venice Charter (1964) gives rise to numerous events around the world. However, many of the issues that currently shape the global heritage landscape are absent from the document, which was drafted in a context very different from our own. This article reflects on the reasons behind the persistent attachment to this charter, with its generalist and universalist ambitions, at a time when a holistic approach to heritage is expected to emerge from fragmented knowledge. After examining the specific historical moment in which the document was written, the text considers the challenges of applying it in a context marked by the expansion of the heritage field and the increasing globalization of debates. The article concludes by examining the Charter's continued relevance as a point of reference and offering concrete avenues for constructive reflection.